THE RELATIONSHIP BETWEEN STRESS LEVELS AND HYPERTENSION INCIDENCE AMONG POLICE OFFICERS IN THE SAMAPTA UNIT OF KAPUAS POLICE DEPARTMENT - Vianetria Vianetria; Ahmad Syahlani; Angga Irawan (Fakultas Ilmu Kesehatan, Universitas Ibn Khaldun, Bogor, 2026)
Hypertension is one of the most prevalent cardiovascular diseases worldwide, including in Indonesia. One of the contributing factors to hypertension is stress, especially among individuals with high work pressure, such as police officers. The Samapta Unit of Kapuas Police Department has complex and high-risk duties, which increase stress levels and may impact their overall health. This study aims to analyze the relationship between stress levels and the incidence of hypertension among police officers in the Samapta Unit of Kapuas Police Department. This research employs a quantitative design with a cross-sectional approach. The study sample consists of all officers in the Samapta Unit of Kapuas Police Department who met the inclusion criteria, totaling 36 respondents. Data were collected using the Perceived Stress Scale (PSS-10) questionnaire to measure stress levels and sphygmomanometer measurements to assess blood pressure. Data analysis was conducted using the Chi-Square test and Fisher’s Exact Test. The results show that 50% of respondents experienced mild stress, 47.2% had moderate stress, and 2.8% had severe stress. Additionally, 38.89% of respondents were diagnosed with hypertension. The statistical test using Fisher’s Exact Test yielded a p-value of 0.009, indicating a significant relationship between stress levels and hypertension incidence among police officers in the Samapta Unit of Kapuas Police Department. These findings confirm that stress levels are significantly associated with hypertension among police officers. Proper stress management strategies should be implemented to reduce the risk of hypertension among law enforcement personnel.